IN SEARCH OF PRONOUN EQUIVALENCE: CHALLENGES IN TEACHING INTERPRETING - Prihantoro Prihantoro (Sanata Dharma University Yogyakarta, 2017)
There are some challenges in Interpreting; in this study, we focus more on the interpreting of pronouns from English as Source Language (SL) to Indonesian as Target Language (TL). The data was collected within simulations in classroom setting. The results showed many unnatural translation of pronoun ‘it’ and ‘this’. References of these pronouns are anaphoric and may take different linguistic units (clause, phrase, word). There were some strategies employed to achieve natural interpreting in TL. Some students repeated the reference(s); but they need to recover the whole references (might be very challenging when the reference(s) are complex). Other strategies are partial recovery, or lexical addition that complies with TL structure. There are some suggestions for an interpreter to deal with the challenges; one of them is to be familiar with the topic of what they are interpreting. In this way, they do not have to rely on short-term memory skills to decide which strategy to employ.